Ethics of psychotherapist deception. Issue 8 (16th November 2020) - Curtis, Drew A.; Kelley, Leslie J.
ABSTRACT: Since Tolman's efforts to establish a code for psychologists, the American Psychological Association's (APA) ethics code has been maintained and revised for over six decades. One of APA's five core principles is honesty and integrity. Recent research has found that therapists lie to patients. The current project explored therapists' and non-therapists' beliefs about the ethics of therapist deception. We recruited 245 students and 38 therapists who read and rated vignettes of therapists lying or being honest. Overall, participants judged therapist deception as unacceptable and unethical. The results of therapist honesty perceived as most ethical and acceptable align with APA's value of honesty and integrity for the profession. Given findings from previous research suggesting the use of deception by psychotherapists, psychologists' ethics code would benefit by addressing honesty and integrity in more detail within the context of psychotherapy.